Influence of oxidative homeostasis on bacterial density and cost of infection in Drosophila–Wolbachia symbioses. (1st April 2016) - Monnin, D.; Kremer, N.; Berny, C.; Henri, H.; Dumet, A.; Voituron, Y.; Desouhant, E.; Vavre, F.
Abstract: The evolution of symbioses along the continuum between parasitism and mutualism can be influenced by the oxidative homeostasis, that is the balance between reactive oxygen species (ROS) and antioxidant molecules. Indeed, ROS can contribute to the host immune defence to regulate symbiont populations, but are also toxic. This interplay between ROS and symbiosis is notably exemplified by recent results in arthropod– Wolbachia interactions. Wolbachia are symbiotic bacteria involved in a wide range of interactions with their arthropods hosts, from facultative, parasitic associations to obligatory, mutualistic ones. In this study, we used Drosophila – Wolbachia associations to determine whether the oxidative homeostasis plays a role in explaining the differences between phenotypically distinct arthropod– Wolbachia symbioses. We used Drosophila lines with different Wolbachia infections and measured the effects of pro‐oxidant (paraquat) and antioxidant (glutathione) treatments on the Wolbachia density and the host survival. We show that experimental manipulations of the oxidative homeostasis can reduce the cost of the infection through its effect on Wolbachia density. We discuss the implication of this result from an evolutionary perspective and argue that the oxidative homeostasis could underlie the evolution of tolerance and dependence on Wolbachia .